Phenylethanoids from the Roots of Codonopsis cordifolioidea and Their Anti HIV-1 Activities - Shen, Yanqiong; Yao, Jianhua; Shu, Lidan; Yang, Liying; Gao, Xuemei; Hu, Qiu-Fen (Asian Journal of Chemistry, 2013)
A new phenylethanoid, 3,4-dihydroxyphenethyl-5-hydroxy-4-oxopentanoate (1), together with four known phenylethanoids (2-6), were isolated from the roots of Codonopsis cordifolioidea. Their structures were determined by means of HR ESI MS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. Compounds 1-6 were tested for their anti HIV-1 activities. Compounds 1 and 3 showed obvious anti HIV-1 activities with therapeutic index values above 50.